The Role of Supervision of Tribal Health Protocols of the Tourism and Creative Economy Office of the East Jakarta Administrative City towards the Hospitality Industry During the Covid-19 Pandemic in the Matraman District of the East Jakarta - Gagih Pradini; Anisa Putri Kusumaningrum; Fitri Agustiani; Nova Nur Rizkia (CV ODIS, 2022)
The existence of the Covid-19 pandemic has made hotels a place that is very vulnerable to virus transmission. Policies from the Government are needed to regulate and supervise health protocols in the hotel industry so that the transmission of Covid-19 can be prevented. This study the object of the study was the hotel industry located in the Matraman District, East Jakarta Administrative City. The Tribe of the Tourism and Creative Economy Office of the East Jakarta Administrative City has a role and responsibility in this supervisory activity. The hotel to be studied is 2 (two) samples and involves several tourists visiting these hotels. The method used is descriptive by triangulation of data interviewing 3 (three) parties to ensure the correctness of the data obtained. Researchers want to know the role of supervision of health protocols carried out by the tourism and creative economy offices of the East Jakarta administrative city on the hotel industry during the covid-19 pandemic in the Matraman subdistrict of the city of administrative east Jakarta